Curriculum Design for Muhammadiyah At-Tanwir Digital Islamic Boarding School: Desain Kurikulum untuk Sekolah Islam Asrama Digital Muhammadiyah At-Tanwir - Hidayah, Ashadi; Nurdiyansyah, Nurdiyansyah (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Islamic boarding schools are key institutions for character and religious education in Indonesia. Specific Background: Muhammadiyah At-Tanwir Digital Islamic Boarding School integrates traditional pesantren education with digital technology to meet modern challenges. Knowledge Gap: Limited studies have explored how pesantren can develop a curriculum that is both faithful to Islamic values and adaptive to technological change. Aim: This study aims to design a curriculum that aligns with the school’s vision, mission, and educational standards. Results: The curriculum integrates religious and general subjects, language practice, tahfidz, entrepreneurship, and extracurricular leadership training, delivered both online and offline. Novelty: This study presents a holistic and integrative digital pesantren curriculum model combining formal, informal, and experiential learning components. Implications: The findings may serve as a reference for other Islamic boarding schools seeking to modernize while maintaining Islamic identity. Highlight: Integrative and holistic digital pesantren curriculum Combination of religious, general, and entrepreneurial subjects Leadership and character-oriented education Keywords: Digital Pesantren, Curriculum Development, Islamic Education, Leadership, Muhammadiyah